Central European stream ecosystems : the long term study of the Breitenbach - Wagner, Rüdiger; Marxsen, Jürgen; Zwick, Peter; Cox, Eileen J. (John Wiley & Sons, 2011)
This is an astonishing book and a great achievement by the small band of scientists who have written it. The Max Planck Society's "Flußstation" (River Station) was active from 1951 to 2006 at Schlitz, in Hessen in central Germany, focused on the ecology of a single small stream, The Breitenbach (in English "Wide Brook.") This concentration of effort was partly because the larger River Fulda, of which the Breitenbach is a first order tributary, had become very polluted, and it offered a more "pristine" ecosystem for study. The program was initiated by two giants of early stream ecology: Joachim Illies was the founder of the "river zonation" school of lotic ecologists and Karl Müller was the originator of the eponymous "Müller's colonization cycle". Their pioneering work was carried on by a small team of scientists (five at any one time) plus assistants, mainly under the leadership of Peter Zwick, and this book is a testament to their dedication, persistence, and skill. This book is a unique compendium of detailed information on a stream, crucially including the underlying--now publicly accessible--data. The next generation of students should exploit and pore over this material because quality and reliability (of taxonomy and methodology) shine through the pages; these were all very highly skilled aquatic ecologists working with the best equipment, and the results are the best.